MENANGANI PENOLAKAN KARYAWAN MELALUI ADKAR MODEL - Eisye Tandelilin (Journal of Management and Business, 2006)
More and more organizations today face a dynamic and changing environment. This, in turn, is requiring these organizations to adapt. “Change or die" is the rallying cry among today's managers worldwide. There are many forces that are acting as stimulants for change such as socio-cultural, technological, economic, and political. But the question is “what can a change agent change?1' The options essentially fall in four categories : structure, physical setting, technology, and people. The application of planned changed is not a simple way and sometimes create many resistances for many reasons. Resistance is not always a negative perspective. The member's resistance can be positive perspectives because it provides a degree of stability and predictability to behavior. There are many tactics have been suggested for use by change agents in dealing with resistance to change. One of the best suggestions is ADKAR MODEL (Awareness, Desire, Knowledge, Ability, and Reinforcement). The advantages of this model are ability to identified why the change is not running well and suggestions to handle it, ability to identify the changing of many levels (individual, group, inter-group, and organization). and the impact of change relatively permanent. The optimal results can be reached if every step in this model is running well and fully supported by all management teams (in system and financial).